2021
DOI: 10.1029/2020gl092264
|View full text |Cite
|
Sign up to set email alerts
|

Topographic and Ground‐Ice Controls on Shallow Landsliding in Thawing Arctic Permafrost

Abstract: An increase in Arctic shallow landsliding is a potential consequence of climate warming. Warmer summer‐air temperatures and larger rainfall events drive heat into the active layer, melting ice and decreasing soil shear stress. Topography has the potential to exacerbate landsliding by controlling the distribution of ground ice and the movement of water in the subsurface. We demonstrate that shallow Arctic landslides initiate in zero‐order drainage basins consistent with models of shallow landsliding in non‐perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Therefore, the part of the permafrost that was thawing on September 21, 2018 had not thawed in the previous 14 years (Figure 8c). This could have resulted in a rapid increase in excess pore-water pressure 18,[54][55][56] facilitating slope failure.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the part of the permafrost that was thawing on September 21, 2018 had not thawed in the previous 14 years (Figure 8c). This could have resulted in a rapid increase in excess pore-water pressure 18,[54][55][56] facilitating slope failure.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work modelling slope stability of thawing permafrost hillslopes found that high concentrations of ground ice near to the potential failure plane had more influence over the slope's stability compared to high ground ice volume in general or the pace at which thawing proceeded (Mithan et al, 2021). In this model, however, the only source of excess pore-water pressures was the thawing ice lenses themselves, with no representation of upslope hydrology channelling either meltwater from upslope ice lenses or any precipitation-derived moisture.…”
Section: Ground Ice Thaw Versus Summer Rainfall As Driver Of Thermokarstmentioning
confidence: 99%
“…In Arctic, sub-Arctic, and Antarctic regions, the presence of permafrost and seasonal thaw lead to a range of soil transport processes strongly influenced by the thermal dynamics of the landscape (Harris and Lewkowicz, 2000;Matsuoka, 2001;Millar, 2013). Water and sediment fluxes are also influenced by the presence of excess near-surface ground ice (Li et al, 2021;Mithan et al, 2021), and limited subsurface infiltration of surface waters due to the presence of impermeable permafrost and seasonally frozen ground (Walvoord and Kurylyk, 2016). As with non-permafrost regions, rates, mechanics, and timing of downslope soil movement on hillslopes play a fundamental role in landscape evolution (Lavé and Burbank, 2004;Roering et al, 2007), the transport and storage of soil organic carbon (Yoo et al, 2006), the delivery of sediment, carbon, and nutrients to streams (Berhe et al, 2018), and the stability of infrastructure (Hjort et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 12 shows the formation and melting of multiple ice lenses and the evolution of the fracture phase field during the numerical freeze-thaw test. Here, we use a scaling factor of 5 while the color bar illustrated in Figure 12A represents the value of the indicator function 𝜒 𝑖 defined in Equation (11). As illustrated in Figure 13 31) although the freezing front still propagates towards the bottom.…”
Section: Freeze-thaw Action: Multiple Ice Lens Growth and Thawing In ...mentioning
confidence: 99%
“…In the United States alone, it was estimated that two billion dollars had been spent annually to repair frost damage of roads 6 . Moreover, extreme climate change over the last few decades has brought increasing attention to permafrost degradation, since unusual heat waves may cause weakening of foundations and increase the likelihood of landslides triggered by the abrupt melting of the ice lens 7–11 . Under these circumstances, both the fundamental understanding of the ice‐lens growth mechanisms and the capacity to predict and simulate the effect beyond the one‐dimensional models becomes increasingly important.…”
Section: Introductionmentioning
confidence: 99%